Students’ Perceptions of ChatGPT: Usability and Enjoyment in English Language Education - Desak Gede Wahyu Puspadnyani; Made Hery Santosa; Luh Indrayani (STKIP AGAMA HINDU SINGARAJA, 2026)
The rapid development of artificial intelligence has influenced English language learning practices, particularly through the integration of ChatGPT as a learning support tool. This study investigates students’ perceptions of ChatGPT’s usability and explores their learning experiences when using the tool in the English Language Education Study Program. The population consisted of 941 undergraduate students enrolled in the program. Using simple random sampling and Slovin’s formula with a 10% margin of error, 90 students were selected as research participants. A sequential explanatory mixed-methods design was employed. Participants used the free version of ChatGPT (GPT-3.5) for one academic semester to support tasks such as writing assignments, idea development, grammar checking, and understanding linguistic concepts. Its use was integrated into coursework and guided by lecturers to promote critical and responsible engagement. Quantitative data were collected using the System Usability Scale (SUS), while qualitative data were obtained through semi-structured interviews with four purposively selected students to gain deeper insight into their experiences. Descriptive analysis revealed an average SUS score of 63, indicating marginal usability. This suggests that although ChatGPT is perceived as beneficial, its usability has not yet reached an optimal level for academic purposes. Interview findings indicated that participants described generally positive learning experiences, including increased confidence, reduced anxiety, and assistance in developing writing skills. However, these qualitative insights reflect individual perspectives and do not constitute a measured level of enjoyment across the broader sample. Several challenges were identified, including occasional inaccuracies, overly general responses, and the potential for overreliance without adequate pedagogical supervision.